Construction of a scale to assess psychological well-being in high school students - Valverde Llamacponcca, Melanie (2021)
Objective: To construct a Psychological Well-being Scale (EBP-VLLM) for high school students of public educational institutions of Independencia. Material and methods: The type of study was instrumental. The instrument went through two phases, the preliminary version of the scale was constituted by 39 items rigorously analyzed, after having been applied in a pilot of 100 students, the content validity indicators were verified and a value p > 0,80 which resulted in a total of 37 items. A sample of 1100 students was selected, which was obtained by a systematic random probabilistic sampling. The data were studied through the analysis of the items taking into account the descriptive statistics. After applying the instrument in the selected sample, 13 items were removed, leaving a total of 24 items. Results: Construct validity was performed through confirmatory factor analysis, which allowed to verify the relevance of the theoretical model, resulting in a scale composed of six dimensions according to the theory of Carol Ryff, Casullo and Seligman, which comprise 50 % of the explained variance; while reliability by internal consistency was obtained through McDonald’s Omega coefficient obtaining a value of 0.846 and the Alpha coefficient obtaining a value of 0.842. Finally, scales were built for the interpretation of the scale, with levels: very low, low, high and very high. Conclusion: The Psychological Well-being Scale (EBP-VLLM) demonstrates adequate indices of validity and reliability for its application.